Pesantren and Entrepreneurship: Thematic Map and Conceptual Implication - Marlina, Lina (SMART Insight, 2024)
Pesantren not only function as religious educational institutions, but also develop as centers for economic empowerment and entrepreneurship based on Islamic values. This research aims to map the development of global research related to the theme of Islamic Boarding School & Entrepreneurship, identify the main thematic clusters, and formulate future research and development directions. The method used is a descriptive qualitative approach through meta-analysis and bibliometrics-based literature studies on 51 Scopus indexed journal articles. The analysis was performed using the VOSviewer software to visualize the keyword, author, and research cluster maps. The results of the study showed six main clusters, namely character education and social entrepreneurship, governance and effectiveness of pesantren management, the role of pesantren in poverty alleviation, pesantren entrepreneurship orientation, productive waqf for the sustainability of pesantren, and leadership and integrated learning system. These findings confirm that pesantren entrepreneurship plays a strategic role in building economic independence, strengthening the character of students, and empowering the community, as well as contributing to the achievement of the Sustainable Development Goals (SDGs). This research provides a conceptual contribution in the form of a comprehensive research map that can be a reference for academics, pesantren managers, and policy makers.